Antecedents and Consequences of Brand Image and Customer Satisfaction on Smartphone Purchase Decisions - Maharani Azis, Tasya (Golden Ratio of Mapping Idea and Literature Format, 2021)
This research results in a study showing that the strength of a product's brand affects job pursuits. The results of this study also rely on digital marketing in its business which has an increasingly significant impact on promotion and positioning. The results of this study can also show that celebrity trust has a positive effect on brand credibility, and this effect is moderated by consumer ethnicity, without the influence of age or gender. Based on the study results, it is concluded that this approach presents the possibility of smartphone-based colorimetric detection in practical applications. And the results also confirm a positive direct and indirect relationship between online destination brand experience (BE), perceived online destination brand credibility (PODBC), and user behavioral intentions towards destinations (recommend). Mapping article use 20 of manuscript form scopus databased index in year 2020. The proposition in this mapping are H1: The reference group positively and significantly affects consumer purchasing decisions. H2: Reference groups can be a part that can construct latent variables of external factors. H3: External factors have a positive and significant effect on brand image. H4: External factors positively and significantly impact consumer purchasing decisions. H5: Brand image has a positive and meaningful direct relationship with consumer purchasing decisions. H6: Customer satisfaction directly, positively, and meaningfully correlates with consumer purchasing decisions. H7: The reference group variable is the variable that has the most dominant influence on consumer purchasing decisions.